The Amazing World of Englishes : a Practical Introduction. - Maier, Georg (Mouton textbook., 2012)
This textbook invites you on a trip around the globe, uncovering layerby layer the complex, yet intriguing facets of English spoken world-wide. The busy streets of London, the scorched vistas of Australia, the colourful and noisy landscapes of New Delhi - English can be heard everywhere. But what are the specific features of these Englishes? What cultural and sociolinguistic realities underlie their use? This textbook brings this exciting and ever-changing world of Englishes right to your door!